Assessment of Project Risk Performance of Selected Mass Housing Infrastructures in Northern Nigeria - Adindu, Chinedu Chimdi; Muhammed, Abdulhaqq Onoruoyiza; Egila, Emmanuel Ashem; Mohammed, Musa (CSID Journal of Infrastructure Development, 2024)
Mass housing projects in Northern Nigeria often suffer from insufficient risk management, impacting timely delivery, budget adherence, and quality standards. This study assesses risk vulnerabilities in selected mass housing infrastructure projects, focusing on information risks related to roles, responsibilities, scope, requirements, and operations. A mixed-methods approach was employed, with data collected from 465 construction professionals across 20 states, with a 64.58% response rate. Analytical tools, including regression and Pearson correlation, identified critical risks such as underfunding, weak project monitoring and control, and the failure to deliver end-user value. Findings reveal that these risks significantly undermine project outcomes, highlighting the need for robust risk management strategies. A risk management framework is proposed to prioritize and address these vulnerabilities throughout the project lifecycle. This research contributes to the field by offering actionable insights for policymakers and practitioners to enhance mass housing delivery, ensuring alignment with end-user needs and project goals.